1987
DOI: 10.1037/0022-006x.55.6.883
|View full text |Cite
|
Sign up to set email alerts
|

The effects of relaxation training with cognitive or nondirective therapy and the role of relaxation-induced anxiety in the treatment of generalized anxiety.

Abstract: Thirty volunteers who met criteria for generalized anxiety disorder received 12 sessions of training in progressive muscular relaxation. Sixteen of the clients also were given cognitive therapy during 10 of those sessions, and the remaining 14 received nondirective therapy. Therapy was provided by 16 graduate student clinicians. The group as a whole showed substantial reductions in anxiety as measured by psychiatric assessor ratings, questionnaires, and daily self-monitoring, although relaxation plus cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
5

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(62 citation statements)
references
References 32 publications
2
54
1
5
Order By: Relevance
“…Existing cognitive behavioural treatments of GAD appear to produce only modest effects (e.g. Butler et al, 1987Butler et al, , 1991Borkovec et al, 1987;Borkovec and Costello, 1993;Durham et al, 1994). The present model helps to explain the modest response rate for CBT interventions.…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…Existing cognitive behavioural treatments of GAD appear to produce only modest effects (e.g. Butler et al, 1987Butler et al, , 1991Borkovec et al, 1987;Borkovec and Costello, 1993;Durham et al, 1994). The present model helps to explain the modest response rate for CBT interventions.…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…Moreover, comparisons with a ''psychological placebo'', a pill placebo or comparable control group conditions showed that CBT has not only unspecific psychotherapy effects, but also specific ingredients (Borkovec et al 1987;Borkovec and Costello 1993;Linden et al 2005;Power et al 1990;Stanley et al 2003). In one study, CBT for GAD was superior to a wait list, but was not more effective than a psychological placebo (Wetherell et al 2003).…”
Section: )(D)mentioning
confidence: 99%
“…Rokovec et al (1987) found that cognitive behavior therapy was superior to nondirective plus relaxation therapy in student sample, while Borkovec and Mathews (1988) found that the effects of two treatments were similar at posttest and 12 months follow up with clinical sample. Clients with generalized anxiety disorder frequently show symptoms of depression Chambless and Gillis (1996, p.122) compared three studies of different researchers and found CBT to have greater impact on depression than behavior therapy (Butler et al, 1991); CBT was superior to nondirective therapy but not to applied relaxation (Borkovec &Costello, 1993); further Borkovec et al(1987) showed that there were no significantly superior CBT effects for depression among treatment completers. Further more Arakawa (1997) showed the efficacy of progressive muscle relaxation to reduce nausea, vomiting and anxiety induced by chemotherapy.…”
Section: Introductionmentioning
confidence: 99%